The association of diabetes with Alzheimer's disease biomarkers and vascular burden across European aging and memory clinic cohorts - van Gils, Veerle; Jansen, Willemijn J.; van der Flier, Wiesje M.; Martinez-Lage, Pablo; Hort, Jakub; Ramakers, Inez H. G. B.; Rouaud, Olivier; Laakso, Markku; Engelborghs, Sebastiaan; Popp, Julius; Lleó, Alberto; Wallin, Anders; et al. (Alzheimer's and dementia, 2025)
INTRODUCTION It remains unclear whether diabetes mellitus (DM) is associated with Alzheimer's disease (AD) pathology and associated vascular burden. METHODS We included cognitively normal (CN), mild cognitive impairment (MCI), and dementia individuals. We assessed associations between DM and AD biomarkers (amyloid beta [Aβ], phosphorylated tau-181 [p-tau181], total tau [t-tau], and medial temporal atrophy [MTA]) and vascular burden (white matter hyperintensities, microbleeds) by logistic regression. Secondary analyses assessed associations between DM and profiles of Aβ combined with p-tau181/t-tau/MTA/white matter hyperintensity/microbleeds. RESULTS We included 5550 participants (65.8+-8.7 years, 8.7% DM). DM was associated with lower odds of abnormal AD biomarkers: Aβ in MCI (odds ratio [OR] = 0.70, 95% confidence interval [CI]: 0.51-0.95, p = 0.02) and dementia (OR = 0.44, 0.26-0.78, p = 0.003), and p-tau181 in dementia (OR = 0.64, 0.41-1.00, p = 0.045). Secondary analyses indicated associations of DM with abnormal t-tau (OR = 1.57, 1.00-2.46, p = 0.048) and MTA (OR = 1.96, 1.05-3.68, p = 0.04) only in CN individuals with normal Aβ. DISCUSSION In cognitively impaired individuals, DM was associated with lower odds of Aβ pathology, whereas DM was associated with neurodegeneration markers in CN individuals without Aβ pathology. Highlights Diabetes mellitus (DM) was associated with lower odds of amyloid beta (Aβ) and phosphorylated tau (p-tau) pathology across clinical populations. DM was associated with total tau and medial temporal atrophy in cognitively normal individuals without Aβ pathology. DM may be associated with dementia through neurodegenerative pathways other than Alzheimer's disease.